How does corruption affect public debt? An empirical analysis - Arusha Cooray; Friedrich Schneider (Johannes Kepler University of Linz, Department of Economics, 2013)
This paper examines the relationship between corruption and public debt in 106 countries. Results suggest that corruption leads to an increase in public debt. We also investigate if the effect of corruption on pblic debt is increased by government expenditure, the shadow economy and military expenditure. We find that the effect of corruption on public debt is compounded by increased government expenditure and increased size of the shadow economy.
Keywords: D78; E26; H2; H11; H26; K42; O5; O11; O16; O17; 330; corruption; public debt; government expenditure; shadow economy; military expenditure